Recent geodetic unrest at Santorini Caldera, Greece - Newman, Andrew V. (2013)
After approximately 60 years of seismic quiescence within Santorini caldera, in January 2011 the volcano reawakened with a significant seismic swarm and rapidly expanding radial deformation. The deformation is imaged by a dense network of 19 survey and 5 continuous GPS stations, showing that as of 21 January 2012, the volcano has extended laterally from a point inside the northern segment of the caldera by about 140 mm and is expanding at 180 mm/yr. A series of spherical source models show the source is not migrating significantly, but remains about 4 km depth and has expanded by 14 million m3since inflation began. A distributed sill model is also tested, which shows a possible N-S elongation of the volumetric source. While observations of the current deformation sequence are unprecedented at Santorini, it is not certain that an eruption is imminent as other similar calderas have experienced comparable activity without eruption.